2018
DOI: 10.1108/ijilt-11-2017-0116
|View full text |Cite
|
Sign up to set email alerts
|

An extension of Delone and McLean IS success model with self-efficacy

Abstract: Purpose While many researchers have investigated the adoption and usage of online learning in different settings, one area that has yet to be examined thoroughly, particularly in the context of online learning in Yemen, is the self-efficacy role. The purpose of this paper is to extend the Delone and McLean information system success model by incorporating a self-efficacy construct as an antecedent to user satisfaction and actual usage to predict student performance. Design/methodology/approach Questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
80
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 72 publications
9
80
1
4
Order By: Relevance
“…Supervisor support is proposed between the relationship of employee intention to adopt technology and employee job performance in such a way that the positive relationship between employee intention to adopt technology and employee job performance will be stronger when supervisory support is higher. Earlier studies have confirmed that supervisor support influence on employee intention to adopt information technology and employee job performance (Aldholay, et al, 2018;Bandura, et al, 1999;Choi, 2004;Makokha & Ochieng, 2014;Samar Rahi & Abd. Ghani, 2018;Tierney & Farmer, 2002;Y.-S. Wang & Liao, 2008;Yu, 2012).…”
mentioning
confidence: 89%
“…Supervisor support is proposed between the relationship of employee intention to adopt technology and employee job performance in such a way that the positive relationship between employee intention to adopt technology and employee job performance will be stronger when supervisory support is higher. Earlier studies have confirmed that supervisor support influence on employee intention to adopt information technology and employee job performance (Aldholay, et al, 2018;Bandura, et al, 1999;Choi, 2004;Makokha & Ochieng, 2014;Samar Rahi & Abd. Ghani, 2018;Tierney & Farmer, 2002;Y.-S. Wang & Liao, 2008;Yu, 2012).…”
mentioning
confidence: 89%
“…Navimipour & Soltani (2016) defined user satisfaction as the sum of positive and negative user (subjective) experiences to a particular information system. A previous study from Aldholay et al (2018) established a meaningful relationship between overall quality and user satisfaction with regards to online learning students in Yemeni.…”
Section: The Relationship Of Perceived Ease Of Use and Perceived Usefulnessmentioning
confidence: 93%
“…Prior studies from Alzahrani, Al-Karaghouli, & Weerakkody ( 2017) and Aldholay et al (2018) suggest that the greater the overall quality that consist of system quality, information quality, and service quality of newer technologies, the more likely that these will enhances desires and lifestyles of their users. Montesdioca & Maçada (2015) referred to user satisfaction as the degree to which users confident and believes that a system meets their needs.…”
Section: The Relationship Of Perceived Ease Of Use and Perceived Usefulnessmentioning
confidence: 99%
See 1 more Smart Citation
“…T AbdelghaffarT &T MagdyT (2012)T[29]T impliesT thatT awarenessT isT theT firstT stepT towardsT usersT knowingT thatT theT governmentT providesT itsT servicesT overT theT InternetT technology.T TheT lackT ofT awarenessT hasT aT negativeT impactT onT citizens'T intentionsT toT adoptT e-governmentT andT m-governmentT servicesT[24].T InT viewT ofT that,T itT canT arguablyT saidT thatT theT lackT ofT awarenessT leadsT toT aT declineT inT interestT inT smartT governmentT services,T andT therebyT users'T satisfaction.Furthermore,T theT qualityT ofT information,T system,T andT servicesT providedT byT smartT governmentT initiativesT areT saidT toT beT havingT aT remarkableT impactT onT endT users'T intentionT toT useT andT theirT satisfactionT[30].T ThisT isT clearlyT evidentT fromT informationT systemT successT modelT developedT byT aT studyT[10].InTaddition,T trustT andT publicT safetyT canT beT concernedT asT aT crucialT determinantT ofT theT satisfactionT ofT beneficiariesT ofT smartT governmentT services.T SmartT CityT IndicatorT surveyT conductedT byT JohnsonT Controls,T pointT outT theT trustT andT publicT safetyT asT oneT ofT theT importantT driversT ofT smartT cityT initiativesT allT overT theT world.T AT modelT ofT trustT andT riskT inT e-governmentT adoption,T whichT wasT proposedT byT [25]T canT beT usedT toT reviewT theT aboveT claim. Finally,T accordingT toT AlmuraqabT &T M.T JasimuddinT (2017)T [24],T socialT influenceT isT theT degreeT toT whichT anT individualT perceivesT importantT thatT otherT peopleT suchT asT familyT andT friendsT believeT heT orT sheT shouldT useT theT newT system.T ItT isT vitalT toT realizeT theT importanceT ofT theT influenceT ofT friendsT andT familyT onT decisionsT toT useT aT technology.T SocialT influenceT isT emergingT asT aT factorT inT theT intentionT toT useT smartT governmentT servicesT asT theT communitiesT areT increasinglyT usedT advancedT ICTsT inT theirT dailyT activities.T Hence,T suchT factorsT canT beT categorizedT asT anotherT dimensionT influencingT theT levelT ofT user'sT satisfactionT overT smartT governmentT servicesT [27].…”
mentioning
confidence: 99%